2012
DOI: 10.1136/annrheumdis-2011-201264
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-detected synovial abnormalities are frequent in clinically inactive juvenile idiopathic arthritis, but do not predict a flare of synovitis

Abstract: The authors found that ultrasound-detected synovial abnormalities are common in children with JIA in clinical remission. However, the presence of ultrasound pathology did not predict an early flare of synovitis in the affected joints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 34 publications
4
86
0
4
Order By: Relevance
“…Therefore, normal amount of synovial fluid and non-specific hypoechoic thickening of synovium/tenosynovium detected in the majority of non-arthritic joints in healthy subjects should not be considered as pathologic or clinically significant. In fact, 6 of 11 causes of false-positives identified in the literature refer to non-specific synovial fluid or thickening (Table 1) [33,35,[37][38][39][40]. In addition, although not included in our systematic literature review, Hiraga et al recently demonstrated that non-arthritic metatarsophalangeal (MTP) joints usually exhibit intraarticular lowechoic area on ultrasound in the dorsal aspect [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, normal amount of synovial fluid and non-specific hypoechoic thickening of synovium/tenosynovium detected in the majority of non-arthritic joints in healthy subjects should not be considered as pathologic or clinically significant. In fact, 6 of 11 causes of false-positives identified in the literature refer to non-specific synovial fluid or thickening (Table 1) [33,35,[37][38][39][40]. In addition, although not included in our systematic literature review, Hiraga et al recently demonstrated that non-arthritic metatarsophalangeal (MTP) joints usually exhibit intraarticular lowechoic area on ultrasound in the dorsal aspect [44].…”
Section: Discussionmentioning
confidence: 99%
“…The second search identified a total of 1329 articles, of which 828 were original articles in English ( Figure 1). Screening process, however, identified only 11 articles that are relevant to sonographic false-positives of synovial/tenosynovial inflammation and none for bursitis [30][31][32][33][34][35][36][37][38][39][40].…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…29 Joint fluid is often used as a marker of disease in adults, 29 but this clearly demonstrates that joint fluid alone cannot be used as a marker of JIA. MagniManzoni et al 30 found ultrasound abnormalities in nearly 36% of healthy children including joint effusions, synovial hyperplasia and a single case of tenosynovitis. These are believed to be normal occurrences secondary to growth and development of the paediatric skeleton.…”
Section: Definitionmentioning
confidence: 99%
“…4). Проведено немало исследований, под-тверждающих как сам факт наличия явления субклиниче-ского синовита, так и его относительно частую встречае-мость [17][18][19], что не позволило экспертам достигнуть единого мнения о безусловной клинической значимости этого феномена.…”
Section: субклинический синовитunclassified